EntrenaPro 360, una aplicación móvil para la planeación de los entrenamientos en las escuelas juveniles de fútbol en Bogotá (2024)
This project seeks to generate a means to facilitate the planning of personalized training for youth soccer schools in the city of Bogota, where they can also analyze the results and evaluate the evolution of the team both collectively and individually. For this reason, the idea was to develop a prototype of a mobile application that fulfills the function of planning training, in this case, in the Independiente Central school in the city of Bogota